Brief Intervention Training for Smoking Cessation in Substance Use Treatment - Egan, Sarah; Allsop, Steve; Daws, C. (John Wiley & Sons Ltd., 2013)
The treatment of nicotine dependence in individuals with substance use disorders has been an area of neglect and contributes to morbidity and mortality. Lack of staff training and education is the most frequently reported barrier to providing smoking cessation treatment in alcohol and other drug (AOD) treatment services. This study assessed the effectiveness of brief intervention training for smoking cessation for staff in AOD treatment services. Participants were recruited from one residential AOD Therapeutic Community, which received the intervention, and the results were compared with participants from two other centres, where no intervention was delivered. Results demonstrated that intervention training increased confidence and willingness to intervene, which are predictive of adopting tobacco interventions in AOD treatment services. This is important as providing more smoking cessation intervention in AOD centres is needed in order to decrease mortality and morbidity related to smoking in AOD clients. Findings indicated however that training did not increase motivation to intervene, and future research is required to determine effective ways to increase staff motivation to address smoking cessation in AOD services.